Konsep Al-Maslahat Al-Mursalah Menurut Imam Al-Ghazali Dan Imam Malik (Studi Eksklusif Dan Inklusif) - M. Najich Syamsuddini (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2022)
Abstract:Al-Maslahat al-Mursalah became a study of the intellectual treasures of muslims for a long time, broadly speaking This article discusses the concept of al-Maslahat al-Mursalah Imam al-Ghazali and Imam Malik in the aspect of exclusive and inclusive study of theories. first: imam al-Ghazali and imam Malik agree that al-Maslahat al-Mursalah as the theorific of the establishment of islamic law then in principle al-Maslahat al-Mursalah should not contradict the main texts (Quran and hadith), rational and absolute, the application of teory al-Maslahat al-mursalah is only used in social aspects, not the field of worship. Second: The exclusive study of al-Maslahat al-Mursalah is covered from the concept of al-Ghazali which places al-maslahat al-Mursalah as a method of Islamic law and as a resource of independent Islamic law and also al-Ghazali's point of view that al-Maslahah al-Mursalah is used for daruriyat or hajj at the same level as daruriyat. Third: The inclusive study of al-Maslahat al-Mursalah is derived from the concept of Imam Malik where the use of al-maslahat al-mursalah as a source of Islamic law and as an independent Islamic resource, and also al-Maslahat al-Mursalah can be used both for daruriyat and hajj. Keywords: al-Maslahat al-Mursalah, Imam Malik, Al-Ghazali , exclusive and inclusive.